Work motivation, job satisfaction and turnover intention of middle level management at five star hotels in Kuala Lumpur / Nur Dalila Mohd Fisol - Mohd Fisol, Nur Dalila (2013)
The hospitality and tourism is one of the largest economic contributors for Malaysia (Economic Impact, 2012). Malaysia is emerging as a fast growing free market economy with services as the main source of economic growth accounting for almost three quarter of Malaysia’s output with 26 percent of its labor force (MIS Asia, 2010). In general, by 2020, there will be a total of 1.6 billion jobs in the hotel industry (Travel & Tourism, 2011). Thus, there is a significant need in having a more qualified, motivated and skilled manpower available to meet the challenges of this ever changing and demanding industry (Ahmad, Aziz, Kamaruddin, Aziz & Bakhtiar, 2012). Similar to the developed countries, hotels in Malaysia are facing problems in attracting and retaining skilled and knowledgeable of high and low level employees. This is due to low salary and rigid job traits (Ahmad, Solnet & Scott, 2010). The rapid expansion of the hotel industry has exaggerated the demand for employment of competent employees (Ahmad & Zainol, 2011), and this resulted in skilled and knowledgeable workers shortages (Business Monitor International Ltd., 2010). On the other hand, the shortage of skilled workers in Malaysian hotels is caused by the unattractive work atmosphere and unmotivated factors of the industry (Kasimu, Zaiton & Hassan, 2012).